ANALISIS KINERJA DENGAN PENDEKATAN INDEKS SHARPE PADA REKSA DANA SYARIAH PENDAPATAN TETAP - Yulis Nurul Aini; Baroroh Lestari; Yekie Senja Oktora (ITB AAS INDONESIA Surakarta, 2022)
This study aims to Understand how the performance of fixed income sharia mutual funds in the Indonesia Capital Market. The research data was obtained from published on the Indonesia Stock Exchange and information Bareksa in the form of financial reports for the period 2018-2020. The financial statement is analyzed using Index Sharpe to explain the performance of fixed income Sharia mutual funds. The result of this study indicates the performance of fixed income sharia mutual funds is in negative performance in 2018-2020.